The Speed-Reading Technique to Boost English as Foreign Language Learners’ Text Comprehension (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Nowadays, many English as Foreign Language (EFL) learners still have problems comprehending the texts they are reading. This article aims at reviewing the speed-reading technique as one of the techniques to boost EFL learners’ text comprehension. A qualitative descriptive research design was applied for the present study. The data were obtained through a documentation study and used state-of-the-art sources in the related studies. Furthermore, the literature review was used to elucidate the findings from the previous studies and related to the present review. The data were analyzed qualitatively by describing how the speed-reading technique can boost learners’ text comprehension. It initiates with information about a brief of speed reading, the development, and trends of speed reading, then describes the speed-reading purposes and movement. The speed-reading techniques to be acquired by the EFL learners are described thoroughly. Besides, the benefits and several implications of speed reading for the Indonesian EFL learners in the classroom practice are highlighted. Finally, this article provides some conclusions and recommendations on what teachers, students, and government can do to boost EFL learners’ text comprehension.